Functional Andromonoecy in Euphorbia (Euphorbiaceae) - NARBONA, E. (Ann Bot, 2002)
The occurrence of cyathia containing staminate flowers but lacking a pistillate flower was studied in 17 species of Euphorbia. Male cyathia were found in the majority of species studied (88·2 %) giving functional andromonoecy. In the male cyathia, the pistillate flower is generally totally absent, but sometimes a vestigial pistillate flower with a non‐functional ovary is present. The proportion of male cyathia varied at both the population and species level. The position of male cyathia within the inflorescence showed a constant pattern among species: the proportion of male cyathia decreased from the first to the last levels of the pleiochasia. In general, perennial species had significantly higher proportions of male cyathia than annual species (mean 20 and 2·3 %, respectively). In annual species there was a trend for production of male cyathia only in the first level of the inflorescence, whereas in perennials production up to the fourth level of the inflorescence was usual. Functional andromonoecy is common in Euphorbia and represents a new sex segregation in the genus. The selective forces causing this secondary sex segregation in Euphorbia, such as improved pollination or increased outcrossing, are discussed.